The heartfelt communication model of the 'Gerakan Indonesia Membantu' in enhancing awareness among Indonesian students in China - Jandevi, Uspal; Lestari, Puji; Prayudi, Prayudi (Informasi, 2024)
This research aims to discover the latest philanthropic communication model employed by the Gerakan Indonesia Membantu (GIM) organization during their efforts to provide aid to Indonesian students in need in China. The spirit of providing tangible support to Indonesian students from lower-middle economic backgrounds, enabling them to continue their studies in China, inspired the formation of the GIM organization. In fulfilling its mission, GIM communicates with various parties so that Indonesian students in China can help one another, with the hope that all Indonesian students in the country can live decently and concentrate on completing their studies successfully This study evaluates and develops the efforts made by the GIM organization in providing assistance, awareness campaigns, and support to Indonesian students who need help to sustain their lives and complete their studies in China. The research adopts a qualitative approach with a phenomenological research type. Data were collected through interviews, focus group discussions, observations, and documentation. The collected data were then processed and conclusions were drawn. The results of this study show that GIM's awareness activities are not only focused on fundraising but also on building public trust in fund management and fostering a sense of belonging among donors towards Indonesian students in need in China. Further explanations are detailed in nine key points discussed in the findings and discussion chapter of this paper. This paper can serve as a reference for social organization activists with humanitarian visions and missions in conducting fundraising activities. It also provides new insights for scholars studying organizational communication, particularly in relation to philanthropic activities.